Svenska smågrisproducenters rutiner kring smågrisdödlighet : utredning av dödsorsak, analys och åtgärder - Sandberg, Linda (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
There are different ways to keep pigs for meat production and legislation differ for example between Sweden and the rest of Europe. Swedish sows are not allowed to be confined in a farrowing crate and the age at weaning for piglets in Sweden is minimum 4 weeks and 3 weeks according EUs legislation.